Promoting private sector for development : the rise of blended finance in EU aid architecture - Mah, Luís (2018)
Since 2007, the EU has been pushing for blended finance to mobilise private sector for development. This is a novel and controversial financial policy coinciding with the growing debate on “beyond aid” and the emergence of new financial tools and actors that are actively engaged with the global development agenda. Since the 1960s, grants and concessional loans (or more simply, aid) have been the dominant type of development finance provided by the EU, together with debt relief and the costs of technical assistance. But aid is no longer the main source of development finance for most developing countries, now replaced by private financial flows: foreign direct investment (FDI), remittances and philanthropy. Business-led economic growth is at the core of the 2030 global development agenda seen as the primary driver of investments, jobs creation and production of goods and services. In consequence, the EU is moving to combine aid with other public and private resources (blended finance) to catalyse and leverage additional funds from the private sector. This paper will critically analyse the emergence and evolution of EU blended finance to support the private sector to deliver the Sustainable Development Goals (SGDs) by 2030 and the potential implications for EU development cooperation.